2018
DOI: 10.1111/let.12238
|View full text |Cite
|
Sign up to set email alerts
|

A Gondwanan perspective on the Ordovician Radiation constrains its temporal duration and suggests first wave of speciation, fuelled by Cambrian clades

Abstract: This study presents a Cambrian–Ordovician (Cambrian, ‘Series 3’ – Katian, Ka4) brachiopod α‐diversity curve for the Iberian terrane. Three diversity pulses characterized the northern Gondwanan margin through the studied interval; an initial increase in linguliformean diversity that culminated during the Tremadocian (Tr3); a second, Darriwilian (Dw2) pulse caused primarily by a rise in orthid species; and a third pulse during Katian times (Ka3–4) marking the most diverse and phylogenetically complex faunas reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Research reported herein focuses on the upper Los Cabos Group and Luarca Formation in the Leonese Mountains and the Armorican Quartzite, Castillejo Formation, and Fombuena Formation in the Eastern Iberian Chain (Figures 2 and 4). Collectively, these units record accumulation from the Floian to middle Katian (ca 478-449 Ma; Figure 4; Pérez Estaún et al, 1990;Gutiérrez-Marco et al, 1999;Cole et al, 2017;Colmenar and Rasmussen, 2017). Detrital zircon provenance analysis suggests sediment was derived from both the West African and Saharan cratons, placing the Iberian shelf near northern Africa (Figure 3;Díez Fernández et al, 2010;Pastor-Galán et al, 2013;Shaw et al, 2014).…”
Section: Stratigraphymentioning
confidence: 99%
See 2 more Smart Citations
“…Research reported herein focuses on the upper Los Cabos Group and Luarca Formation in the Leonese Mountains and the Armorican Quartzite, Castillejo Formation, and Fombuena Formation in the Eastern Iberian Chain (Figures 2 and 4). Collectively, these units record accumulation from the Floian to middle Katian (ca 478-449 Ma; Figure 4; Pérez Estaún et al, 1990;Gutiérrez-Marco et al, 1999;Cole et al, 2017;Colmenar and Rasmussen, 2017). Detrital zircon provenance analysis suggests sediment was derived from both the West African and Saharan cratons, placing the Iberian shelf near northern Africa (Figure 3;Díez Fernández et al, 2010;Pastor-Galán et al, 2013;Shaw et al, 2014).…”
Section: Stratigraphymentioning
confidence: 99%
“…Ironstone occurs in the Herrera Unit of Álvaro et al (2018b). Pale red colour in stratigraphic column highlights approximate depositional age of ironstone (Gutiérrez-Marco et al, 1999;Cole et al, 2017;Colmenar and Rasmussen, 2017). The base of ironstone in the Peña del Tormo and Marité members is locally erosive.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…The early history and evolution of the phylum have, not surprisingly, a strong influence on the composition and shape of the curve. There are strong peaks reported from along the northern Gondwanan margin, during the Tremadocian, dominated by linguliform brachiopods; at the same time, the diversification of the Cambrian evolutionary fauna continued in shallow‐water siliciclastic facies (Colmenar & Rasmussen ). During the same interval in tropical Gondwana (South China), orthide and syntrophide faunas flourished prior to the massive spike in diversity during the Darriwilian (Zhan & Harper ).…”
Section: Biodiversification(s) At the Level Of Individual Groupsmentioning
confidence: 99%
“…Around Gondwana, the onset and development of the GOBE are charted in Ordovician successions of the Iberian Peninsula by Colmenar & Rasmussen (), with an initial increase in the diversity of linguliformean brachiopods that culminated as early as the Tremadocian, followed by pulses of rhynchonelliform diversification in the Darriwilian and Katin. Lefebvre et al .…”
Section: Regional Diversificationsmentioning
confidence: 99%